Strategic Management Research Trends In The Creative Industries: A Bibliometric Approach - Ridwan Harun, Andy Suryani, Nurzaitu Afia, Vervasia Yohana Delima, (YUME : Journal of Management, 2024)
The creative industry plays an important role in the global economy and is growing rapidly, especially in the digital era which is characterized by technological advancements and innovation. This study aims to analyze research trends in strategy management in the creative industry using a bibliometric approach. This approach allows for the exploration of publication patterns, collaborations, and research dynamics over time. Using VOSviewer software, the study identified 229 selected publications from the Dimensions database with the keywords "Strategic Management" and "Creative Industries" in the period 2016-2025. The results of the analysis show fluctuations in the number of publications, with a significant spike in 2024. The study also highlights the key countries that contributed to this publication, including the United Kingdom, China, and Russia, as well as the institutions involved such as the Politecnico di Milano and the Pontifical Catholic University of Peru. These findings provide an in-depth overview of key topics and provide insights for researchers and practitioners in developing more effective and innovative strategies in the creative industries. Keywords: Bibliometrics; Strategic Management; Creative Industries